2011
DOI: 10.1002/pon.1798
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making preferences and information needs among Greek breast cancer patients

Abstract: This study's findings showed that the proportion of patients who wanted to play a passive role in decision making is the highest reported compared to similar studies from other countries, indicating the impact of the dominating paternalistic model of the doctor-patient relationship in the Greek medical encounter. The association of desired information details and decision-making preferences with screening for cancer procedures prediagnostically highlights the significance of providing the patients with the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
3
28
1
5
Order By: Relevance
“…Results from the study shows that older breast cancer patients made treatment decisions on their own. This finding is inconsistent with a previous study who found that older breast cancer patients were more comfortable to leave the treatment decisions to the physician or assume a less active role in making treatment decisions (Pinquart and Duberstein, 2004;Gaston and Mitchell, 2005;Almyroudi et al, 2010;Shelton et al, 2012).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Results from the study shows that older breast cancer patients made treatment decisions on their own. This finding is inconsistent with a previous study who found that older breast cancer patients were more comfortable to leave the treatment decisions to the physician or assume a less active role in making treatment decisions (Pinquart and Duberstein, 2004;Gaston and Mitchell, 2005;Almyroudi et al, 2010;Shelton et al, 2012).…”
Section: Discussioncontrasting
confidence: 98%
“…A review of literature on decision-making and information provision in patients with advanced cancer pointed out that those who took an active role were younger and had a higher education level (Gaston and Mitchell, 2005). Younger and more educated women were likely to prefer more active roles (Almyroudi et al, 2010).…”
Section: Older Women Breast Cancer Survivors: Decision Making Sourcementioning
confidence: 99%
“…[3233] A Study conducted in Greece suggested that while women expressed a general desire for as much information as possible about their illness, majority of women play a passive role in treatment decision-making and delegate responsibility of the decision completely to their doctor. [34]…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have been conducted in non‐U.S. contexts, such as in Australia , China , Germany , Greece , Jordan , Spain , and the United Kingdom . This is important because cultural differences shape breast cancer patients’ information needs .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of studies involve patients' self-reports of information needs [23], which are only tenuously correlated with what patients actually ask about during consultations. Most of these studies have been conducted in non-U.S. contexts, such as in Australia [24], China [25,26], Germany [26], Greece [27], Jordan [28], Spain [29], and the United Kingdom [30,31]. This is important because cultural differences shape breast cancer patients' information needs [23,26,32].…”
Section: Introductionmentioning
confidence: 99%